Fundamentalisme Pendidikan Islam dan Eksistensinya Dalam Dunia Pendidikan : Studi Pemikiran Kh. M. Hasyim Asy’ari Dan Kh. Imam Zarkasy - Nia Daniati Arum Kusumastuti; Rustam Ibrahim; Ainul Luthfia Al Firda (Universitas Islam Sultan Agung, 2023)
Fundamentalism of the leadership of an educational institution will continue to give birth to new generations based on the basic concepts of education and teaching. Two well-known figures in Islamic education, KH M. Hasyim Asy'ari and KH Imam Zarkasyi, have brought major changes to education in Indonesia. This can be seen and tested from the quality of alumni. Therefore this study is important to find out the basic concept of Islamic education leadership that it applies, as well as its relevance in maintaining its existence in the world of education. The research approach uses a qualitative descriptive approach. This type of research is library research with data collection methods obtained from books, journals, research results and others. This research resulted in the concept of Islamic education leadership according to KH M. Hasyim Asy'ari and KH Imam Zarkasyi which refers to the values of Islamic boarding schools, including essential and instrumental values. Each of these essential values and instrumental values has different points that are tailored to the goals of each educational institution.